Upaya Revitalisasi Wisata Alam Curug Gondoriyo Melalui Peningkatan Kompetensi Dan Motivasi Berbasis Komunitas - Vicky Oktavia; Almira Santi Samasta; Maria Safitri (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the development of community-based tourism in Curug Gondoriyo, Semarang. A SWOT analysis is employed to identify the strengths, weaknesses, opportunities, and threats of the destination. Curug Gondoriyo possesses significant ecotourism potential, supported by its pristine natural environment and the active involvement of the local community in its management. Since the onset of the Covid-19 pandemic, Curug Gondoriyo has experienced a drastic decline in tourist visits, posing challenges to development efforts, sustainable management, and community regeneration. Based on the SWOT analysis, the formulated strategy involves adopting a collaborative cross-sectoral approach to enhance the competence and motivation of managers, strengthening promotion through digital tourism management training, and revitalizing the spirit of mutual cooperation to improve physical facilities, accessibility, and supporting infrastructure. These strategies serve as key drivers for fostering positive socio-economic impacts while preserving environmental sustainability. The implication of this study is the development of an adaptive, innovative, and sustainable community-based ecotourism model with the potential to improve the welfare of the local community by ensuring the conservation of natural and cultural resources..